1991
DOI: 10.1093/brain/114.3.1197
|View full text |Cite
|
Sign up to set email alerts
|

Word Deafness and Auditory Cortical Function: A Case History and Hypothesis

Abstract: SUMMARYA patient who already had Wernicke's aphasia due to a left temporal lobe lesion suffered a severe deterioration specifically of auditory language comprehension, subsequent to right temporal lobe infarction. A detailed comparison of his new condition with his language status before the second stroke revealed that the newly acquired deficit was limited to tasks related to auditory input. Further investigations demonstrated a speech perceptual disorder, which we analysed as due to deficits both at the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 79 publications
1
37
0
1
Order By: Relevance
“…In the cognitive model [15] ( Figure 1) this impairment in phoneme processing corresponds to a disorder at the lower perceptive level of treatment: the auditory analysis system (Figure 1). It leads to failure of access to higher levels (lexical and semantic) and can be sufficient to explain impairment of oral comprehension without disorders of the auditory input lexicon or of the semantic system [38,39]. In this patient, brain damage did not involve the temporal lobes, unlike lesions classically described in word deafness [3], but it was located in the brainstem and in the white matter [10,11] which partly disconnect the auditory cortex from the auditory nucleus and disrupts the initial auditory process.…”
Section: Discussionmentioning
confidence: 99%
“…In the cognitive model [15] ( Figure 1) this impairment in phoneme processing corresponds to a disorder at the lower perceptive level of treatment: the auditory analysis system (Figure 1). It leads to failure of access to higher levels (lexical and semantic) and can be sufficient to explain impairment of oral comprehension without disorders of the auditory input lexicon or of the semantic system [38,39]. In this patient, brain damage did not involve the temporal lobes, unlike lesions classically described in word deafness [3], but it was located in the brainstem and in the white matter [10,11] which partly disconnect the auditory cortex from the auditory nucleus and disrupts the initial auditory process.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have characterized patients' speech perception deficits using psycholinguistic measures (Saffran et al 1976;Auerbach et al 1982;Miceli 1982;Tanaka et al 1987; Yaqub et al 1988;Praamstra et al 1991). These studies unfortunately revealed no uniform performance, as illustrated in Table 2; therefore it is not possible to attribute specific phonetic or phonological deficits to the syndrome.…”
Section: Psycholinguistic Assessments Of Word Deafnessmentioning
confidence: 99%
“…Evidence for a rapid temporal processing deficit in verbal auditory agnosia comes from the observation that individuals with verbal auditory agnosia often have particular difficulty with temporally dynamic aspects of speech stimuli, such as place of articulation and voicing contrasts in consonants, compared to temporally protracted aspects of speech such as vowels (Saffran et al, 1976;Auerbach et al, 1982;Miceli, 1982;Yaqub et al, 1988;Praamstra et al, 1991;Wang et al, 2000;Stefanatos et al, 2005a;Slevc et al, 2011). Verbal auditory agnosia also is associated with pronounced deficits in perception of rapid temporal changes in non-speech stimuli (Fig.…”
Section: Apperceptive Verbal Auditory Agnosiamentioning
confidence: 99%